Public–private innovation: barriers in the case of mobility as a service in West Sweden. Issue 1 (2nd January 2019) - Smith, Göran; Sochor, Jana; Karlsson, I.C. MariAnne
ABSTRACT: Departing from open innovation (OI), this case study explores the development of Mobility as a Service (MaaS) in West Sweden. An analysis of 19 interviews reveals how representatives from involved actors perceive internal and external barriers as hampering the regional public transport authority's attempts to collaborate with private actors, and that the perception of barriers is incongruent across public and private actors. Transferability to other cases of public–private OI is discussed, and implications for public actors are proposed. The paper expands the knowledge of preconditions for MaaS' development and of the unique conditions for OI in public–private settings.